‘Forced to Leave’: Aspects of Ethnic, National, and Transnational Identity of Political Migrants from Belarus after 2020 - Frėjutė-Rakauskienė, Monika (Information & Media, 2025)
The aim of this article is to discuss the situation of political migrants from Belarus in Lithuania. The article presents data collected during field research (semi-structured and unstructured life story interviews with migrants) in Vilnius and Kaunas. The article focuses on people persecuted for their political beliefs in Belarus who arrived in Lithuania after 2020 as a result of this persecution. The article provides statistics on the number for arrivals, as well as an overview of the policy exerted by Lithuania towards Belarus and those Belarusians who have arrived in Lithuania. The article analyses their migration history, motives for choosing the country, their future perspectives and plans, while emphasizing their identity (ethnic, national, transnational). The article is written within the framework of the project “Ethnic, National and Transnational Identities and Geopolitical Attitudes of Third-Country Nationals in Lithuania in the Context of the War in Ukraine”, funded by the Research Council of Lithuania, LMTLT (No. S-MIP-23-39). The article reveals that political migrants have a Belarussian national identity that has strengthened after the year 2020 protests. This national identity subsumes features of Belarusian ethnic identity which embraces the common origin of these immigrants – Belarus – along with the Belarusian language which they purposefully speak among themselves and in public. Features of transnational identity are also noticeable, since they closely maintained various social ties in Belarus that strengthen their sense of belonging to the Belarusian community, and their future plans are related to a declared desire to return and contribute to the (re)establishment of a democratic Belarus and its institutions.
Keywords: political migrants from Belarus after 2020; migrant attitudes; aspects of identity (ethnic, national, transnational)